2017
DOI: 10.2166/wp.2017.041
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater arsenic in Bangladesh: what's new for policy research?

Abstract: This paper provides an overview of policy responses to arsenic in groundwater in rural Bangladesh to assess their role and potential effectiveness in reducing exposure. With 97% of the country consuming groundwater for drinking, there is a continuing crisis of tens of millions of people exposed to elevated levels of arsenic. An examination of the number of people protected through two major remediation efforts suggests that recent progress may not be sufficient to keep up with the increasing population or to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, the initial national As testing was conducted with As field test kits, which cost just BDT 7,000 for 100 samples. Along with the fact that many newly installed, untested shallow tube-wells have caused around 50% of households to use untested water, this approach may just be the most effective option in the short term [ 6 , 41 ]. However, unless people are aware of the uncertainty in groundwater conditions, they may test their wells just once and assume one clean result is all that is necessary, as suggested by the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the initial national As testing was conducted with As field test kits, which cost just BDT 7,000 for 100 samples. Along with the fact that many newly installed, untested shallow tube-wells have caused around 50% of households to use untested water, this approach may just be the most effective option in the short term [ 6 , 41 ]. However, unless people are aware of the uncertainty in groundwater conditions, they may test their wells just once and assume one clean result is all that is necessary, as suggested by the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…According to the DPHE’s annual report [ 5 ], 87% of the population are secured with community water sources, which include shallow tube-wells, deep tube-wells, pond sand filters, and dug wells. Pipeline water supply is now an option, and the promotion of its construction in As-affected areas was stated in the 2014 National Strategy for Water Supply and Sanitation, although pipeline water supply as a standard component of infrastructure in rural areas of Bangladesh is still a long way off [ 6 ]. Despite the efforts made so far, reports have shown that one-third of these As-safe water options are not in use or have been abandoned [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…They conducted a survey in previously identified arsenic-contaminated areas and found 62% of 32,651 tubewells in 200 villages have arsenic concentrations above 100 µg/L (Smith et al 2000 ). During 1999–2005, the GOB launched a program named BAMWSP (Bangladesh Arsenic Mitigation Water Supply Program) financed by World Bank and screenend (blanket survey) As concentrations in tubewells of 270 uppzillas and stored 4.8 million well arsenic concentration data-points in NAMIC (National Arsenic Mitigation Information Centre) (Johnston and Sarker 2007 ; Balasubramanya and Horbulyk 2018 ).). Approximately 29.1% of those tested tubewells had arsenic concentrations higher than the Bangladesh standard for arsenic content in drinking water (50 µg/L or 50 ppb) (Kabir and Howard 2007 ).…”
Section: Past and Present Arsenic Management Policies And Practices I...mentioning
confidence: 99%